Effects of Recreational Camping on the Environmental Values of National Parks in Sri Lanka - Shashini Tara Mallikage; Priyan Perera; David Newsome; Rangika Bandara; Greg Simpson (Tropical Life Sciences Research, 2021)
Camping is a popular activity in the contemporary nature-based tourism domain and rapidly gaining momentum as a key recreational activity in Sri Lanka’s National Parks (NPs). Recreational uses such as camping in natural areas can induce significant and often localised resource impacts that can affect soil, vegetation, wildlife and water, with the severity of such impacts varying according to the intensity of use. Hence, monitoring of the biophysical conditions of campsites has become an important component in the reserve management agenda in many places, especially in developed countries. To the best of our knowledge, this is the first study to examine the biophysical impacts associated with the recreation ecology of camping in Sri Lanka. Ten campsites from three dry zone NPs were selected to assess biophysical impacts of camping activities. Field measurements were based on the fixed radial transect method. Gathered data included the total area of the campsite, erosion potential measured as the area of exposed soil (devoid of vegetation or organic litter), number of exposed roots and human damage to trees, number of fireplaces/fire scars on the ground, visual counts of litter, soil compaction measured by penetrometer, loss of woody debris. This study reports significant levels of environmental degradation related to all the indictors of biophysical impacts at both high and low use campsites. There was no evidence for any difference in the level of environmental degradation associated with high and low use campsites. The loss of natural values associated with campsites negatively impacted visitors’ nature-based experience. These findings highlight the importance of managing biophysical impacts in campsites to provide a high-quality visitor experience, while sustainably managing tourism activities in NPs.